2007
DOI: 10.1179/174367607x168996
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic synthesis and mechanical properties of hydroxyapatite/poly (vinyl alcohol) nanocomposites

Abstract: Hydroxyapatite/poly(vinyl alcohol) (HAp/PVA) nanocomposite samples were prepared by two different methods of direct mixing and an in situ biomimetic HAp crystallisation in the presence of polymer. Polymer weight fraction was the variant in both procedures. The prepared samples were characterised with regard to their mechanical properties by performing tensile tests on hot pressed samples. The phase composition and microstructural studies were conducted using X-ray diffraction (XRD) and scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Block copolypeptide templates that form gels at very low weight fractions (0.5-4 wt%) compared to previously investigated synthetic block copolymers, allow for inorganic content in the nanocomposites of over 50 wt%, more closely approaching the inorganic content seen in natural bone. Previous research 75,76 has shown that the increase of HAp content will result in an increase in the elastic modulus but a decrease in the tensile strength and ductility. A good compromise of these mechanical properties can be obtained in the composite of HAp weight fraction of 60-70%, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Block copolypeptide templates that form gels at very low weight fractions (0.5-4 wt%) compared to previously investigated synthetic block copolymers, allow for inorganic content in the nanocomposites of over 50 wt%, more closely approaching the inorganic content seen in natural bone. Previous research 75,76 has shown that the increase of HAp content will result in an increase in the elastic modulus but a decrease in the tensile strength and ductility. A good compromise of these mechanical properties can be obtained in the composite of HAp weight fraction of 60-70%, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies on the in situ synthesis of nanometer-scale hydroxyapatite in the PVA matrix have been reported. 11,29,30 The mineralization of hydroxyapatite in biological systems typically occurs in a hydrogel environment. It is helpful to understand the nature of the hydroxyapatite mineralization for the synthesis in a hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome the drawbacks of PVA, many researchers developed PVA nanocomposites with improved properties using inorganic materials as nanofillers. [9][10][11][12][13] Owing to the outstanding mechanical, electrical and thermal properties, carbon nanotubes (CNTs) may be an ideal filler for fabricating nanocomposites. However, CNTs are hydrophobic due to the lack of functional groups on its surface and tend to aggregate together through strong van der Waals interactions, which hinder the dispersion of CNTs in the polymer matrix and limit the applications of CNTs in numerous areas.…”
Section: Introductionmentioning
confidence: 99%